Importance of Youth Involvement in Sports - Caroline Payne; Kate Fogarty (EDIS)
FCS-2278, a 4-page fact sheet by Caroline Payne and Kate Fogarty, will help answer parental questions about when and how children should become involved in organized sports. It also addresses the benefits and possible pitfalls of such activity. Published by the UF Department of Family, Youth and Community Sciences, October 2007.